'Taking the heat' - developing propellants for high-temperature applications - Mohammed, Yahaya (Cranfield University, 2016)
3MT (three minute thesis) presented at the 2016 Defence and Security Doctoral Symposium. Since the early 1800s, nitrocellulose (NC) based propellants have gained popularity due to their low cost, ease of manufacture, and good ballistics. Vehicle airbags, small arms ammunition, aircraft ejection seat, tactical missiles and short to medium range rockets are some of the areas where NC propellants have been applied. Typical homogenous NC-based propellants depending on the energetic constituents are classified as single, double or triple base. Sometimes these propellants are further modified using high explosive additives depending on the performance requirements. The problem with NC, like other nitrate esters, is its poor thermal stability due to the weak RO-NO2 bonds especially, when exposed to high temperature and high humidity conditions as found in sub-Saharan Africa. Similarly, in deep-lying oil wells, NC propellants are problematic due to the high likelihood of ‘cook off'. Several accelerated ageing studies involving the exposure of propellants to high temperatures for the purpose of determining their failure mechanism and stability over time have been conducted. However, few of these studies were focused on the behaviours of NC propellants in tropical, sub-Saharan African climate. This research is aimed at understanding the degradation mechanism of NC propellants (double base) in a typical West African climate. The thesis will be focused on formulating alternative propellant compositions with better performance and thermal resilience. On the completion of the research, it is expected that a new surveillance technique suitable for sub-Saharan African climate will be developed. The first phase of the research will cover the thermal and mechanical analysis of NC propellants in high-temperature environments leading to the design of a bespoke propellant surveillance method for this climate. While the second the phase will cover formulation, characterization and testing of new binder and filler compositions as possible substitutes to NC-based propellants.
Keywords: 'DSDS16 3MT'; 'DSDS16'; 'Propellants'; 'Thermal stability'; 'Cook off'; 'Chemical Thermodynamics and Energetics'